Analysis of visual content in SARS-CoV-2 and Covid-19 news coverage of scientific divulgation in Spanish magazines in the digital environment - De Vicente Domínguez, Aida María (2020)
The visual content in the coverage of COVID-19 in the digital editions of the most consumed Spanish scientific journals during this epidemiologicalcrisis is analyzed. The objectives are to analyze the presence, number, typology, hyperlink and authorship of the image in the informative pieces. The image (n= 549) is analyzed in the informative pieces published in muyinnteresante. es (n= 204) and nationalgeographic.com.es (N=85) from February 7 to May 14, 2020. A content analysis was chosen by previously established codes to identify the variables under study. It is established that the potential of the image is not used in the digital environment and proposals for improvement are made to optimize the potential of the image due to its importance as a source of knowledge in times of health crisis.